Agriculture and intellectual property rights [ economic, institutional, and implementation issues in biotechnology - Santaniello, V. (CABI, 2000)
Plant breeding patents, the ownership of biological innovation and associated intellectual property rights (IPR) are the subject of increased attention worldwide. Particularly relevant to the field of biotechnology, this book presents the perspectives o policy-makers and economists on such issues.